First‐trimester diagnosis of Meckel–Gruber syndrome by fetal ultrasound with molecular identification of CC2D2A mutations by next‐generation sequencing. (27th October 2014) - Jones, D.; Fiozzo, F.; Waters, B.; McKnight, D.; Brown, S.
ABSTRACT We describe a first‐trimester ultrasound examination in which the finding of fetal encephalocele and the cystic appearance of the kidneys raised suspicion of Meckel–Gruber syndrome (MKS). On the basis of sonographic findings, the patient elected termination of pregnancy, and post‐termination studies using next‐generation sequencing of a gene panel revealed two mutations (one previously described and the other novel) in the gene CC2D2A. Mutations in CC2D2A are known to cause MKS and Joubert syndrome, thus providing molecular confirmation of the clinical suspicion of MKS and opening the possibility for future prenatal diagnosis. This case highlights the ability to detect important anomalies in the first trimester using ultrasound, even in low‐risk situations. It also demonstrates the growing role of new sequencing technologies in fetal testing. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.